Operational and structural diagnosis of sewerage and drainage networks in Côte d'Ivoire, West Africa - Ouattara, Zié Adama; Kabo-Bah, Amos T.; Dongo, Kouassi; Akpoti, Komlavi; Siabi, Ebenezer Kwadwo; Kablan, Malan Ketcha Armand; Kangah, Kouamedai Mathias (Frontiers in Sustainable Cities, 2023)
in Cote d’Ivoire, the failure of urban sewage systems is a crucial problem for the drainage of wastewater and rain water. This failure is due to many factors and therefore, calls for diagnostic studies. The present study aimed at analysing these networks in order to identify the different factors that contribute to the functional degradation in selected sewerage and drainage networks in Abidjan, Cote d'Ivoire. The method used in the study involved semi-structured interviews, video camera inspection and socio-environmental field surveys (Geographical survey and household survey), followed by descriptive statistics. The results revealed that many structural, environmental and behavioural practice contribute to the progressive degradation of urban sewage systems. These factors are essentially those that prevent the normal flow of water in the pipes such as the illegal dumping of solid waste, the unauthorized connection of wastewater networks, unsustainable urban agricultural practices and the dilapidated infrastructure of the wastewater and rainwater networks. It was found that these factors are at the origin of the clogging and degradation of the sewers since 85% of the residents used these sewers as a dumping ground for solid waste. Key words: Urban sewerage systems, Malfunction factors, structural factors, anthropogenic factors, Drainage systems.